Fish Consumption and Mercury Exposures Among Sub-populations in Canada through Targeted Biomonitoring: Results from Dene/Métis Communities of the Northwest Territories and a Maternal-Infant Cohort Study - Packull-McCormick, Sara R. (University of Waterloo, 2023)
Fish contain many important nutrients including omega-3 polyunsaturated fatty acids (PUFA) (such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)) and essential elements (such as selenium (Se)), and fish consumption has been associated with various health benefits. However, fish can also be a source of exposure to environmental contaminants, such as mercury (Hg). Fish consumption is considered to be a major source of Hg exposure for the Canadian general population, and this can pose a health risk for populations that consume significant amounts of fish or consume fish containing elevated levels of Hg. This thesis focused on two sub-populations in Canada that may be disproportionately impacted by exposure to Hg (either by being especially exposed to Hg or especially sensitive to the negative effects of Hg). The first was Dene/Métis communities in northern Canada, as these communities frequently consume locally harvested freshwater fish and elevated levels of Hg have been measured in some fish species from some local lakes in northern Canada. prompting concerns about Hg exposure as these populations may be especially exposed. The second sub-population examined was pregnant women and children in Canada, as early life stages are especially sensitive to the neurotoxic effects of Hg as their nervous systems are undergoing rapid development. To address concerns for both of these potentially disproportionately impacted sub-populations, focused biomonitoring projects can be used. In the Northwest Territories, to address concerns about exposure to environmental contaminants, including Hg from local fish, a community-based human biomonitoring project was implemented in First Nations communities in the Dehcho and Sahtú regions of the Northwest Territories. To understand chemical exposures, including Hg, in Canadian pregnant women and children, Health Canada is conducting the Maternal Infant Research on Environmental Chemicals (MIREC) pregnancy cohort study and follow-up studies, which include a biomonitoring ...